Understanding barriers to dTap vaccination recommendations during pregnancy among healthcare workers: Aida Bianco. (25th October 2022) - Bianco, A; Angelillo, S; Riillo, C; Nobile, CGA; Campione, C; Freccia, S; Romeo, M; Licata, F
Abstract: Background: Diphtheria, tetanus and pertussis (dTap) vaccination is heavily endorsed during pregnancy. However, maternal dTap immunization rates in Italy remain low. Lack of healthcare workers (HCWs) recommendation to get vaccinated represents one of the main barriers to immunization during pregnancy. Therefore, this study aimed to investigate what HCWs know about dTap vaccination, practices and potential barrier to recommending immunization during pregnancy. Methods: This cross-sectional study was conducted among obstetricians-gynaecologists (OBs), midwives and general practitioners (GPs) in 2 regions of Southern Italy. An anonymous self-administered questionnaire was used to collect data on professional information, knowledge, risk perceptions and practices regarding dTap vaccination during pregnancy. Results: Until now 94 HCWs were recruited (36.2% OBs, 35.1% GPs and 28.7% midwives). Overall, 63.8% knew that dTap vaccination has to be administered during the third trimester of gestation and 94.7% that it is able to protect newborns against pertussis before active immunization. One-third of the HCWs believed that vaccines in pregnancy were more dangerous than safe. Seven out of ten HCWs routinely recommended dTap vaccine and provided information about dTap vaccination to all pregnant women. Most frequent reported reasons for not recommending dTap vaccination during pregnancy were that it was outside the scope of their practice (72.4%), that women are more vaccine hesitant during pregnancy (42.9%), lack of time (28.6%), lack of knowledge on the topic (28.6%) and the belief that the vaccine could interfere with the development of the fetus (14, 3%). Conclusions: Lack of knowledge, unsatisfactory recommendation of dTap immunization during pregnancy and uncertainty over their responsibility around vaccination suggest that public health organisations should strengthen dissemination and implementation of evidence-based recommendations. Key messages: Barriers to recommending dTap immunization during pregnancy remain among healthcare workers. Strategies (e.g. electronic reminders) to facilitate HCWs in recommending and informing on dTap immunization should be implemented and evaluated to improve vaccination coverage in pregnant women.